Equilibrium and convergence in personal income distribution? How European countries performed during a phase of huge economic turbulence (2004-2017) - Yanling Guo; Friedrich L. Sell (Universität der Bundeswehr München, Fachgruppe für Volkswirtschaftslehre, 2020)
The authors set up a political economy equilibrium framework for personal income distribution. Located in status theory, their concept is able to explain what justifies a certain or optimal degree of inequality in the society. The authors present an empirical analysis of personal income distribution in 23 European countries. The time period covers the years before, during and after the great recession (2004-2017). Linear regressions, which make use of ex-post Gini coefficients, show that the hypothesis of the existence of an equilibrium value for the Gini-coefficient can be weakly confirmed, after controlling for a possible impact from the great recession as well as from EU membership.
Keywords: D31; D60; D63; D71; D72; E62; H23; 330; Political Economy; Personal Income Distribution; Equilibrium; Convergence; Redistributive Policies; Great Recession; EU Membership